Development of Teacher Modules on Learning Locomotor Movement Materials - Rama Kurniawan; Febrita Paulina Heynoek; Dhenok Putri Ragil Mahfud Wijaya (Pusat Kajian Pendidikan Olahraga, Kesehatan, dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2022)
This study aims to develop a locomotor movement learning module at grade 4 of SDLB with autism, in terms of content and attractiveness which is equipped with locomotor movement pictures and videos that can be accessed offline or online. Research and development used the ADDIE model (analysis, design, develop, implement, and evaluate) as the model of development research. The research used a questionnaire instrument in collecting data and use descriptive quantitative as an analysis technique data. Research subjects are SLB Autism of Universitas Negeri Malang and SDLB C Autism Tuban. Consist of teachers and students in these schools. The subjects of the small group trial are 3 SLB teachers and the large group trial consisted of 20 SLB teachers. The result in a large group trial is 95,14%. From this data, the conclusion obtained that the locomotor movement learning module at grade 4 of SDLB with autism for the teacher is very valid to be applied in learning